A Survey on the Prevalence of IVS14 + 1G > A Mutation of the Dihydropyrimidine Dehydrogenase Gene Among a Group of Colorectal Cancer Patients in Northeast Iran, the Relevance of Fluoropyrimidine Based Chemotherapy Toxicity - Sadeghi Ivari, Mahboobeh; Salek, Roham; Hosseini, Bibi Ashraf; Behravan, Javad; Aledavood, Amir (Reports of Radiotherapy and Oncology, 2016)
Background: Dihydropyrimidine dehydrogenase (DPD) is the initial enzyme in the catabolism of 5-fluorouracil (5-fu). Deficiency of this enzyme can lead to severe and lethal toxicity following the administration of 5FU or capecitabine. The aim of this study was to demonstrate the prevalence of the IVS14 + 1G > A mutation of the dihydropyrimidine dehydrogenase gene (DPYD) and important side effects of the adjuvant chemotherapy regimens in an ethnic Iranian group of colorectal cancer (CRC) patients. Methods: The research population included patients with colorectal cancer during the period of October 2011 to January 2013. Genomic DNA was isolated from blood cells of 109 patients. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique was carried out to identify the frequency of the IVS14 + 1G > A mutation. The side effects of chemotherapy regimens containing 5-FU or capecitabine were recorded during 1-6 courses of chemotherapy. Results: The IVS14 + 1G > A mutation was not found in the population studied. Overall 28.4% of patients reported to have at least 1 grade 3 or 4 toxicity. Conclusions: We concluded that IVS14 + 1G > A mutation was rare in the population studied; however, a larger sample size may be required to determine the precise mutation frequency in this region.